Research of the Influence on the Modification of Beryllium in Al–Si Alloy - Hren, I.; Michna, S.; Drozdyk, L.; Cais, Jr.; Michnova, L.; Svobodova, J.; Hodinár, L. (Металлофизика и новейшие технологии, 2018)
Modification of molten metal is performed for the eutectic and subeutectic silumins prior to its casting by using strontium, which has a time-limited effect up to 1–1.5 hours. Beryllium is used in order to prolong the modifying effect. The aim of the experiment is to examine both the distribution and the effect of beryllium in the structure on the temporary extension of the modification in the Al–Si alloys in combination with strontium modifier. Перед отливкой расплавленного металла выполняется модифицирование эвтектических и субэвтектических силуминов с помощью стронция, который имеет ограниченный 1–1,5 часами временный эффект воздействия. Бериллий используется для продления модифицирующего эффекта. Целью эксперимента является изучение распределения и влияния бериллия в структуре на временное продление модифицирующего воздействия в сплавах Al–Si в сочетании со стронциевым модификатором. Перед відливанням розтопленого металу виконується модифікування евтектичних і субевтектичних силумінів за допомогою Стронцію, який має обмежений 1–1,5 годинами тимчасовий ефект дії. Берилій використовується для продовження модифікувального ефекту. Метою експерименту є вивчення розподілу та впливу берилію в структурі на тимчасове подовження модифікувальної дії в стопах Al–Si у поєднанні зі стронційовим модифікатором.